Breaking silos of legal and regulatory risks to outperform traditional compliance approaches - Haelterman, Harald (European journal on criminal policy and research, 2022)
The ever-evolving legal and regulatory landscape and resulting pressure on organizations to adapt and comply is just one of many factors that have turned compliance management into a crucial yet increasingly complicated activity. In recent years, numerous compliance challenges have been reported on and traditional approaches for managing legal and regulatory risks are increasingly being scrutinized. This paper provides an overview of the main challenges faced by commercial organizations and goes on to focus on what is referred to as a holistic, integrated approach to managing compliance. It explores the key characteristics and suggested benefits of the approach, as well as some factual and more substantive arguments in support of its claims and underlying logic. Borrowing from criminological theory, it further argues that despite the potential benefits of a holistic view of compliance, there equally remains room for caution.